The alchemyst - Scott, Michael, 1959- (Thorndike Press, 2007)
While working at pleasant but mundane summer jobs in San Francisco, fifteen-year-old twins, Sophie and Josh, suddenly find themselves caught up in the deadly, centuries-old struggle between rival alchemists, Nicholas Flamel and John Dee, over the possession of an ancient and powerful book holding the secret formulas for alchemy and everlasting life.